2019
DOI: 10.5194/gmd-2019-278
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Configuration and Intercomparison of Deep Learning Neural Models for Statistical Downscaling

Abstract: Abstract. Deep learning techniques (in particular convolutional neural networks, CNNs) have recently emerged as a promising approach for statistical downscaling due to their ability to learn spatial features from huge spatio-temporal datasets. However, existing studies are based on complex models, applied to particular case studies and using simple validation frameworks, which makes difficult a proper assessment of the (possible) added value offered by these techniques. As a result, these models are usually se… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
14
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
7
2

Relationship

2
7

Authors

Journals

citations
Cited by 14 publications
(14 citation statements)
references
References 31 publications
0
14
0
Order By: Relevance
“…A limited amount of machine learning studies has been reported in terms of downscaling of air temperatures Baño-Medina et al, 2019; Sachindra and Kanae, 2019 , whereas considerable success has been achieved in downscaling of precipitation e.g., Wilby et al, 1998;Vandal et al, 2017;Misra et al, 2018;Baño-Medina et al, 2019;Pan et al, 2019 . Gaps between model formulas and actual events of rainfall processes may be greater than those in temperature, and hence, there may be still room for the contribution of machine learning.…”
Section: Use Of Machine Learning Techniques In Meteorologymentioning
confidence: 99%
See 1 more Smart Citation
“…A limited amount of machine learning studies has been reported in terms of downscaling of air temperatures Baño-Medina et al, 2019; Sachindra and Kanae, 2019 , whereas considerable success has been achieved in downscaling of precipitation e.g., Wilby et al, 1998;Vandal et al, 2017;Misra et al, 2018;Baño-Medina et al, 2019;Pan et al, 2019 . Gaps between model formulas and actual events of rainfall processes may be greater than those in temperature, and hence, there may be still room for the contribution of machine learning.…”
Section: Use Of Machine Learning Techniques In Meteorologymentioning
confidence: 99%
“…Another important moiety to be addressed is spatial estimation, namely, downscaling. Several studies have attempted to apply these techniques to meteorological downscaling and demonstrated their effectiveness in terms of air temperatures Baño-Medina et al, 2019;Sachindra andKanae, 2019 , precipitation e.g., Wilby et al, 1998;Vandal et al, 2017;Misra et al, 2018;Baño-Medina et al, 2019;Pan et al, 2019 , andwind speeds Li, 2019 . Most of these earlier studies focused on obtaining variables at a grid spacing of approximately 10 -50 km by downscaling large-scale variables simulated by general circulation models.…”
Section: Introductionmentioning
confidence: 99%
“…In climate science, deep learning has recently been applied to a number of different problems, including microphysics (Seifert and Rasp, 2020), radiative transfer (Min et al, 2020), convection (O'Gorman and Dwyer, 2018), forecasting (Roesch and Günther, 2019;Selbesoglu, 2019;Weyn et al, 2019), and empirical-statistical downscaling (Baño-Medina et al, 2020). For example, Yuval et al (2021) have applied deep learning for parametrization of subgrid scale atmospheric processes like convection.…”
Section: Introductionmentioning
confidence: 99%
“…Notable efforts have been made in order to assess the credibility of regional climate change scenarios. In the particular case of SDS, a plethora of methods exists nowadays, and a thorough assessment of their intrinsic merits and limitations is required to guide practitioners and decision makers with credible climate information (Barsugli et al, 2013). In response to this challenge, the COST Action VALUE (Maraun et al, 2015) is an open collaboration that has established a European network to develop and validate downscaling methods, fostering collaboration and knowledge exchange between dispersed research communities and groups, with the engagement of relevant stakeholders (Rössler et al, 2019).…”
Section: Introductionmentioning
confidence: 99%